Recent progress of neuromorphic sensory and optoelectronic systems - San Nam; Donghyun Kang; Jeong-Wan Jo; Dong-Won Kang; Sung Kyu Park; Yong-Hoon Kim (International Journal of Extreme Manufacturing)
With the rise of artificial intelligence (AI), neuromorphic sensory systems that emulate the five basic human sensations including tactility, audition, olfaction, gustation, and vision have attracted significant attention. In particular, research on integrating sensors with artificial synapses is being carried out extensively. These studies offer valuable opportunities for making another breakthrough in AI technology, including autonomous systems, real-time monitoring systems, and human-machine interactions. In this review, we introduce promising reports of neuromorphic sensory systems. Specifically, the core sensing material, device architecture, fabrication process, and applications of the proposed systems are presented in detail. Finally, the unsolved challenges and the prospects of neuromorphic sensory systems are discussed.